2014
DOI: 10.1016/j.ajo.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

New Testing Options for Diagnosing and Grading Dry Eye Disease

Abstract: PURPOSE To describe new options for diagnosis and severity grading of dry eye disease DESIGN Perspective on technological advancements to identify tear dysfunction and their value in diagnosing and grading dry eye disease. METHODS Evidence is presented on new and evolving technologies to measure tear stability, composition and meniscus height and their role in dry eye diagnosis and therapeutic efficacy grading is assessed. RESULTS Evolving concepts regarding pathogenesis and new technologies to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 57 publications
(68 reference statements)
1
34
0
4
Order By: Relevance
“…In addition, tear stability has been traditionally measured using TBUT 23 . Dry eye in pSS can damage the ocular surface, and the range and severity of KCS is assessed using ocular stain score systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tear stability has been traditionally measured using TBUT 23 . Dry eye in pSS can damage the ocular surface, and the range and severity of KCS is assessed using ocular stain score systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that these new methods would be integrated into clinical practice for diagnosis, classification, and severity grading of DEDs in the near future. 24,32,33 Furthermore, symptoms alone are not enough to diagnose and manage DED. A consensus of clinical signs that better captures the totality of DED is needed.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research has shown the validity of tear osmolarity as one of the best objective measures of dry eye. [23][24][25] The observed variability in tear osmolarity between eyes or multiple measurements in the same eye has established a means of identifying patients with mild tear dysfunction, given that such variability is not observed in normal tears. Hence, measuring tear osmolarity may be useful in diagnosing and grading DED severity.…”
Section: Discussionmentioning
confidence: 99%
“…This initiates the vicious circle of dry eye pathology in a final common pathway. Hyperosmolarity induces inflammatory cascade activation [135][136][137], increases apoptosis [138][139][140], and stimulates expression and activity of MMPs [141,142], causing ocular surface barrier disruption [143,144]. In severe cases, dry eye also leads to squamous metaplasia involving ocular surface epithelial cell transdifferentiation from a wet mucosal phenotype to a keratinized skin-like phenotype [145].…”
Section: Ocular Surface Barrier Function In Dry Eye Diseasementioning
confidence: 99%